Mobile Public Transportation Application: Factors Influencing Urban Rail Transit Passengers' Use - Saraswaty, Nur Husnina; Safizahanin, Mokhtar; Muhammad Zaly, Shah Muhammad Hussien; Zuhra Junaida, Mohamad Husny Hamid; Gobi Krishna, Sinniah; Nabila, Abdul Ghani (UNIMAS Publisher, 2022)
This paper thoroughly explored and discussed the factors that affect Mobile Public Transportation Applications usage among urban rail transit passengers. To do so, a model known as the Unified Theory of Acceptance and Use of Technology (UTAUT) was chosen to determine the significant factors influencing mobile application usage among passengers in Klang Valley, Malaysia. During its primary data collection, an online survey was deployed to 109 passengers using an online survey platform. According to the modal split analysis, most female students and private-sector employees aged 18-29 years use the Mobile Public Transportation Application with route projection during an emergency, depending on the mobile application facilitating conditions. Moreover, based on the factors analysis' result, facilitating conditions are an essential factor compared to the other constructs. However, the study's findings might be biased towards a certain age and gender group due to its respondent reach. Therefore, an equal number of respondents in various age and gender groups is highly recommended for future research to fully grasp the factors that may affect passengers using the Mobile Public Transportation Application in urban mobility.